Pre-Nicene christology in paschal contexts : the case of the divine Noetic anthropos - Giulea, Andrei-Dragoș, 1975- (Vigiliae Christianae, Supplements, 2013)
In Pre-Nicene Christology in Paschal Contexts Dragoş A. Giulea re-examines the earliest texts related to the festival of Easter in light of Second Temple traditions. Commonly portrayed as sacrificial lamb, the key actor of the paschal narrative is here designated as heavenly Kabod , Divine Image, King of the Powers, celestial Anthropos, Demiurge, Son of Man, each of these divine names implying a corresponding soteriological function. Dragoş A. Giulea indicates as well that the Greek philosophical vocabulary and certain idioms of the mystery religions inspired new categories which reshaped the traditional way of describing the nature of celestial entities and the epistemological capacities able to access these realities. Thus, the King of the Powers, or the Son of Man, is several times described as a noetic Anthropos, while initiation and noetic perception become the appropriate methods of accessing the divine.